Bone Marrow Granuloma in Typhoid Fever: A Morphological Approach and Literature Review - Kavitha Muniraj; Somanath Padhi; Manjiri Phansalkar; Periyasami Sivakumar; Renu G’Boy Varghese; Reba Kanungo (Case Reports in Infectious Diseases, 2015)
Typhoid fever is one of the few bacterial infections in humans where bone marrow evaluation is routinely recommended. However, the morphological aspect of typhoid fever in bone marrow has been rarely described in the literature. We describe a 25-year-old male patient who presented with prolonged fever suspected to be of tubercular etiology. Bone marrow examination showed well-formed histiocytic and epithelioid granulomas and erythrophagocytosis; and the bone marrow aspirate culture grew Salmonella typhi A. In view of potential clinical implications, typhoid fever should be considered as a differential diagnosis to tuberculosis in the evaluation of prolonged fever; especially in high prevalent areas. We suggest that erythrophagocytosis may serve as a morphological marker in typhoid granulomas in the bone marrow; and bone marrow culture should be submitted in every suspected case for appropriate patient management.